Formulasi dan Uji Anti Inflamasi Masker Peel Off Ekstrak Etanol Buah Mengkudu (Morinda citrifolia L.) - Miratun Syarifah; Nining Sugihartini; Laela Hayu Nurani (Fakultas Farmasi Universitas Pancasila, 2019)
Infl ammation of the skin often occurs in acne-prone skin. Acne can be prevented in variousways, one of them by maintaining clean skin. Noni fruit (Morinda citrifolia L.) with the active ingredientof scopoletin has been proven to be eff ective as an anti-infl ammatory. Noni is dried into simplicia,extracted was ethanol 96% solvent until it becomes concentrated extract. The extract is formulated intoa peel off mask with a concentration variation of 5%, 10 and 15%. The masks produced is evaluated forphysical characteristic of pH, viscosity, spreadability, and adhesivity test), as well as anti-infl ammatoryproperties using mice with the parameters of COX-2 expression and irritation test using rabbit. Theevaluation results of the physical characteristic of the peel off mask fulfi lled the physical characteristicrequirements of the peel off mask preparation. Whereas in the viscosity test there were groups thatmet the viscosity requirements, namely the formula I and II groups and the group that did not meet theviscosity requirements, namely the formula III group. Anti-infl ammatory test in mice showed that themask lead to reduction in the amount of COX-2 expression. The best formula in 3 preparations wasindicated in formula I with COX-2 expression value of 22.635%. The results of irritation test on rabbitsdid not cause irritation. According to the test results it can be concluded that the optimum value of theethanol extract concentration is shown in formula I with a concentration of 5%.